Evaluation Report on the Centrally-Sponsored Programme for Improvement of Secondary Education- Strengthening of Science Laboratories and Special Training of Science Teachers - Planning Commission (Planning Commission, 1967)
At a meeting Held in Yojana Bhavan, New Delhi, on the 14th December, 1966, under the chairmanship of the Secretary, Planning Commission, and attended by representatives of Union Ministries of Education and Finance and the University Grants Commission, it was decided to request the Programme Evaluation Organisation of the Planning Commission to make a quick evaluation of the progress of the centrally sponsored schemes relating to the strengthening of science teaching in schools (Crash Programme). Since the Programme Evaluation Organisation was unable to take up this assignment owing to its preoccupation with other enquiries, it was decided to entrust the job to an Evaluation Team consisting of Shri A.H. Hemrajani, Director (Education), Planning Commission and Dr. M. C. Pant, Professor of Science Education in the Deportment of Science Education, National Council of Educational Research and Training.
Planning Commission Government of India
Planning Commission Government of India